Health and the workplace: thinking about sickness, hierarchy and workplace conditions. (20th February 2009) - Yuill, Chris
Health is an inescapable aspect of the workplace. Increasingly, attention is being focused on how the health of all employees could be improved to increase overall business efficiency and to reduce days lost to ill-health. Unfolding in three parts this paper sets out to draw attention to the findings of social scientists who offer informative insights into the various dynamics and interplays of how the workplace conditions health. Firstly, a robust holistic definition of health will be offered to counter reductionist renderings of health. Secondly, findings from longitudinal research will highlight that workplace control and support are often more critical in influencing employee health than 'lifestyle' (smoking, drinking and diet) factors. Thirdly, attention will turn to why a healthy workplace can be hard to realise.